Thermally propagated Al contacts on SiGe nanowires characterized by electron beam induced current in a scanning transmission electron microscope. (29th October 2021) - Conlan, Aidan P; Luong, Minh Anh; Gentile, Pascal; Moldovan, Grigore; Den Hertog, Martien I; Monroy, Eva; Cooper, David
Abstract: Here, we use electron beam induced current (EBIC) in a scanning transmission electron microscope to characterize the structure and electronic properties of Al/SiGe and Al/Si-rich/SiGe axial nanowire heterostructures fabricated by thermal propagation of Al in a SiGe nanowire. The two heterostructures behave as Schottky contacts with different barrier heights. From the sign of the beam induced current collected at the contacts, the intrinsic semiconductor doping is determined to be n-type. Furthermore, we find that the silicon-rich double interface presents a lower barrier height than the atomically sharp SiGe/Al interface. With an applied bias, the Si-rich region delays the propagation of the depletion region and presents a reduced free carrier diffusion length with respect to the SiGe nanowire. This behaviour could be explained by a higher residual doping in the Si-rich area. These results demonstrate that scanning transmission electron microscopy EBIC is a powerful method for mapping and quantifying electric fields in micrometer- and nanometer-scale devices.